2011
DOI: 10.1148/radiol.11102467
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Cancer: Assessment of Complete Response to Preoperative Combined Radiation Therapy with Chemotherapy—Conventional MR Volumetry versus Diffusion-weighted MR Imaging

Abstract: Post-CRT DW MR volumetry provided high diagnostic performance in assessing CR and was significantly more accurate than T2-weighted MR volumetry. Post-CRT DW MR was equally as accurate as volume measurements of both T2-weighted and DW MR. Pre-CRT volumetry and ADC were not reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
227
5
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(252 citation statements)
references
References 27 publications
(36 reference statements)
16
227
5
4
Order By: Relevance
“…Qualitative interpretation of ICC values are as follows: 0 -.20 ϭ poor; 0.21-0.40 ϭ fair; 0.41-0.60 ϭ moderate; 0.61-0.80 ϭ good; and 0.81-1 ϭ excellent. 8 For test-retest reproducibility, these metrics were calculated separately for each reader, and then the metrics from the readers were averaged. Similarly, for interreader reproducibility, these metrics were calculated separately for each acquisition, and then the metrics from the acquisitions were averaged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative interpretation of ICC values are as follows: 0 -.20 ϭ poor; 0.21-0.40 ϭ fair; 0.41-0.60 ϭ moderate; 0.61-0.80 ϭ good; and 0.81-1 ϭ excellent. 8 For test-retest reproducibility, these metrics were calculated separately for each reader, and then the metrics from the readers were averaged. Similarly, for interreader reproducibility, these metrics were calculated separately for each acquisition, and then the metrics from the acquisitions were averaged.…”
Section: Discussionmentioning
confidence: 99%
“…1 In various disease states, DTI has been extensively investigated in brain applications and can detect abnormalities in otherwise normal-appearing brain regions 2,3 and is able to predict outcomes. 4 Early DTI use shows promise in detecting spinal cord abnormalities associated with spinal cord injury, 5,6 demyelinating diseases, 7 spondylotic myelopathy, 8 HIV myelopathy, 9 and various inflammatory and vascular myelopathies. 10 In acute spinal cord trauma, DTI has shown value in assessing microstructural injury, differentiating between hemorrhagic and nonhemorrhagic contusions, and strong correlation with clinical injury scores.…”
mentioning
confidence: 99%
“…The inter-reader agreement of ADC was evaluated with interclass correlation coefficients (ICC). ICC interclass correlation coefficient is interpreted as follows: 0.61-0.80, good agreement; 0.81-1.00, excellent agreement (10). The level of significance was set at P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent diffusion coefficient (ADC) calculated from DW-MRI measurements may be used to quantify and express these properties. The majority of the studies have demonstrated that the pretreatment ADC is negatively correlated with response to treatment (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). It appears that necrotic areas with high pretreatment ADC values may be less sensitive to CRT.…”
Section: Introductionmentioning
confidence: 99%